IMPROVING READING SKILLS AMONG CRITICAL LEVEL STUDENTS THROUGH INVERTED PYRAMID APPROACH - Samuel, Samikkanu Jabamoney Ishak; Muniandy, Rajantheran (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of the study is to improve reading skills in Malay language among critical level students through inverted pyramid approach. Quantitative approach through pre-test and post-test on experimental and control group design was implemented in this study. Simple random sampling was carried out to recruit the study sample comprising 10 Form One students who cannot read in Malay Language in a secondary school from a population of 20 students. The researcher found that the experimental group students had a high score of 979 (97.9%) compared to the control group students of 292score (29.2%). In comparison, these post-test groups recorded a gap of 68.7%. Meanwhile, during pre-test, these two groups only recorded a gap of 1.6%. The findings show that the inverted pyramid approach has improved the reading skills in Malay language among critical students. This study is useful in improving the reading skills among critical level students. This inverted pyramid approach not only is used to teach reading skills but also to teach all skills pertaining to all subjects. Inverted pyramid approach has not been used in teaching any pedagogical skills. This research is the first research on inverted pyramid approach. This approach really works in improving learning skills among the critical level students.